It Contributions to Efficient Transport Management - Anthony Wren (Communications - Scientific letters of the University of Zilina, 2000)
Transport systems revolve around their schedules. Computer scheduling systems are now installed in very many transport organisations, and savings are well documented. These may be: direct savings from more efficient schedules; indirect savings because of the ability provided to investigate speedily alternative scenarios; induced savings where the computer has pointed out how adjustments to timetables or operating rules would increase efficiency. However, the use of an IT system for scheduling does not, in itself, guarantee a good schedule. There are many attractively presented systems that produce poor schedules, often quite quickly. These should be avoided, and it is important that people involved in the choice of systems should appreciate the distinction between good and bad algorithms. We report from our own experience on successful uses of IT for scheduling and show some of the pitfalls.